ERRORS IN TRANSLATION BETWEEN SL INTO TL MADE BY THE STUDENTS OF TRIDINANTI UNIVERSITY OF PALEMBANG - Tridinanti, Gaya; Budiyanto, Darmawan (UNIVERSITAS TRIDINANTI PALEMBANG, 2017)
ABSTRACT: The problems of the research were: 1. What types of grammatical errors were found in the SL into TL Translation made by fifth semester students of English department of Tridinanti University of Palembang? 2.What were the frequency and the percentage of each types of grammatical error in translated texts made by the students? The aims of the study were to describe the errors that were found in the SL into TL Translation writing made by the students of Tridinanti University Palembang, to describe the frequency and the percentage of each type of grammatical errors in translated texts made by the students. In this research the writer used qualitative approach with the documentation technique used to collect the data, and analyze the data used of content analysis. The result of the research based on the surface category taxonomy, the student‘s errors could be classified into: 1) omission, (2) addition, (3) misformation, and (4) misordering errors. 2) Reveal with the frequency and the percentage of each types of grammatical error in translated texts made by the students, the writer found that 0.95 % errors in omission, 0.8 % errors in additions, 0.8 % errors in missformation), 0.75 errors in misordering.Keywords: Errors, translation, SL into TL.